Dinamika Kehidupan Keberagamaan Masyarakat Madura di Kabupaten Bogor - Muh Syamsuddin (Mukaddimah: Jurnal Studi Islam, 2018)
The purpose of this paper is to know and obtain information about the dynamics of Madurese community life in Bogor Regency. From the results of discussion or analysis can be seen that most of the Madurese as a pedangang (entrepreneur). Overall Madura community in Bogor district is very closely related to the religion they embrace the religion of Islam as an identity. This is evident in his daily life which can not be separated from the teachings of Islam. This can be obtained by the idea that Islamic teachings have a pentic role in improving the quality of their daily lives. Such as their personal, social, religious, and economic improvement.